KARAKTERISTIK FISIKOKIMIA DAN SENSORIS MIE BASAH BERBAHAN BAKU TEPUNG SUKUN (Arthocarpus altilis fosberg) dan TEPUNG LABU KUNING (Curcubitha moschata durch) - Geiby Boham; Teltje Koapaha; Judith S.C. Moningka (Universitas Sam Ratulangi, 2015)
ABSTRACT Food diversification is necessary of food development, and breadfruit is able to develop into a variety of food products. Breadfruit contains pretty high carbohydrate that 28.2gr/100gr mature flesh (Fao, 1972 in Gardjito etc 2013), which is very potential to be develop as an alternative to wheat flour in making of varieties of noodle such as fresh noodle. The aim of this research is to get the right formulation of breadfruit flour and pumpkin flour in making of wet noodle, and also to analyze the physical, chemical and sensory quality. The result of this research showed that the best and the dominant formulation is the formula C (80% breadfruit flour and 20% pumpkin flour) which is the most likeable formula. Formula C (80% breadfruit flour and 20% pumpkin flour) contains 25.19% of moisture content, 5,87% of proteins, 0.72% of ash, 32.33 sec of cooking time, 34.67 mins of cooking resistant. The sensory test’s of formula C showed that formula C is acceptable in panelists with scores; 3.46 of color, 3.42 of aroma and 4.08 of taste. Keyword : Breadfruit, Pumpkin, Noodle